The Development of Gravity Comic Learning Media Based on Gorontalo Culture - Ntobuo, N. E.; Arbie, A.; Amali, L. N. (Jurnal Pendidikan IPA Indonesia, 2018)
The aim of the study was to develop Gravity comic learning media based on Gorontalo culture for V grade Elementary School students. The type of the research was developmental referring to the design of 4-D model according to Thiagarajan, Semmel, and Semmel (1974) which consisted of 4 stages; define, design, develop and disseminate. The results of this study indicated that the developed gravity comic are valid and could increase students’ responses to learning. This cultural-based comic introduces Gorontalo regional cultures. The percentage of the students’ active participation was 93.27% for limited trial and the average students’ active participation in field trial was 94.94%. The students’ learning result gave 86.75% of classical completeness data for the limited test class, while the field test class obtained an average percentage of 87.37%, and categorized as very good. Therefore, the developed Comic of Gravity materials was declared valid, practical and effective. In sum, it would be useful for science learning process in grade V of Elementary School.